Ex-vivo release of Pipeline Embolization Device polytetrafluoroethylene (PTFE) sleeves for improved distal landing zone accuracy in-vivo: A technical note. Issue 6 (December 2016) - Griessenauer, Christoph J; Gupta, Raghav; Moore, Justin; Thomas, Ajith J; Ogilvy, Christopher S
Background: Distal landing zone accuracy is critical in some intracranial aneurysms treated with the Pipeline Embolization Device (PED), and delayed opening of the distal end of the device can complicate the procedure. Here, we report a technical nuance that facilitates accurate placement of the distal end of the PED by ex-vivo, pre-implantation release of the PED Flex polytetrafluoroethylene (PTFE) sleeves. Technical note: The PED Flex is partially pushed out of the introducer sheath ex-vivo, pre-implantation until the distal PED opens entirely and the PTFE sleeves are located distal to the device. Without inverting the PTFE sleeves, the PED is carefully pulled back into the introducer sheath placing the PTFE sleeves inside the device. The PED is loaded into the microcatheter and advanced toward the site of implantation. When the PED is initially deployed and pushed out of the microcatheter, it opens immediately and provides an anchor for the remainder of the deployment process. We present a video (supplementary material) that illustrates the technique along with an illustrative case. Conclusion: Ex-vivo, pre-implantation release of the PTFE sleeves is an option in aneurysm treatment where distal landing accuracy is critical. Even without the protection of the PTFE sleeves, our clinical observation shows that the PED can be advanced safely through the microcatheter in selected cases.